The early-life gut microbiome in common pediatric diseases: roles and therapeutic implications - Bankole, Taiwo; Li, Yuanyuan (Frontiers in Nutrition, 2025)
The early-life gut microbiome has been increasingly recognized as a contributing factor for pediatric health and diseases. Studies have reported that the human gut microbiota colonization commences at birth and progresses over the course of the first three years of life, until it reaches a mature and stable diversity and composition. During this critical window, the gut microbiome is vulnerably subjected to environmental factors, leading to transient microbial reprogramming and functional changes. The dynamic early-life intestinal microbiota is frequently manipulated by environmental factors, which impact the composition and function of the gut microflora, hence confer to short-and/or long-term health outcomes extending to adulthood. Evidence has shown that the imbalanced gut microbial community early in life is associated with several childhood diseases and disorders, such as inflammatory bowel diseases, allergies, attention-deficit/hyperactivity disorder and pediatric obesity. Manipulating the early-life intestinal microbes can either ameliorate or impair host’s immunological and metabolic responses, impacting overall health conditions later in life. This narrative review article discusses the recent understanding and implications of the early-life gut microbiome in common pediatric diseases and potential intervention approaches.